Library Volunteers at Gonzaga College High School Library: Motivation and Impact for Students - Fadhilah, Ilyas; Rianti, Fahma (Syarif Hidayatullah State Islamic University of Jakarta, 2023)
This study aims to determine the intrinsic and extrinsic motivation of students as Library Lovers of Gonzaga College High School (PPKG) and the impact felt by students. The method used in this research is qualitative with a case study approach. Determination of informants using purposive sampling technique with a total of 5 informants. Data sources were obtained through interviews, observation, and documentation. Data validity test using source triangulation. The theories used for analysis are Frederick Herzberg's two-factor motivation theory, Janusz Reykowski's prosocial motivation theory, and Clary, et al's volunteer functions inventory (VFI) model. The results of this study show that the motivation most felt by students as library volunteers at Gonzaga College High School Library is extrinsic motivation. This motivation comes from outside oneself and usually there is influence from others, especially from the head of the library as the supervisor of PPKG activities, the existence of healthy interpersonal relationships, reciprocity from the library to the PPKG party, then a safe and healthy workplace, so that this PPKG activity can reduce something negative in its members. Meanwhile, the intrinsic motivation that is felt more than other aspects is that overall PPKG activities have a positive impact on the learning process and learning achievement in class. However, not all felt the impact on their information literacy skills. .